Invaluable knowledge : securing your company's technical expertise - Rothwell, William J. , 1951- (New York : American Management Association, 2011)
As organizations face a loss of people due to retirement, resignation, or disability, leaders are paying attention to their talent management strategies, from grooming internal successors to recruiting from their competitors. This book clarifies the issues of attracting, developing, retaining, and transferring the knowledge of IT professionals
1. Introducing technical talent management -- 2. Conceptualizing the issues in technical talent management -- 3. Recruiting and selecting technical and professional workers -- 4. Developing technical and professional workers -- 5. Retaining technical and professional workers -- 6. Managing and engaging technical and professional workers -- 7. Transferring valuable knowledge: theory and models -- 8. Transferring valuable knowledge: practical strategies -- 9. Tackling future challenges
Includes bibliographical references (p. 195-206) and index
Keywords: Employee retention; Employees -- Recruiting; Information technology -- Management; Knowledge management; Manpower planning